Konseling Individu Dengan Teknik Self-Control Dalam Mengatasi Perilaku Narsisme Remaja Pengguna Tik-Tok Konseli “C” Di Kelurahan Baturaja Permai - Oktivioni, Frisky; Razzaq, Abdur; Jannati, Zhila (Jurnal Ilmu Sosial, Humaniora dan Seni, 2022)
The background of this research is that adolescents who experience narcissistic behavior tend to think excessively of themselves, thereby disturbing the environment and making themselves feel elated. The purpose of this study was to find out the description of narcissistic behavior of adolescents "C" who use tick-tock in the Baturaja Permai sub-district before applying individual counseling with self-control techniques, knowing the application of individual counseling with self-control techniques to counselee "C" who experiences narcissistic behavior and knowing how description of narcissistic behavior in counselee "C" after participating in individual counseling with self-control techniques. This study used a qualitative approach with a case study research method. The subject of this research is counselee "C". Data collection techniques are observation, interviews, and documentation. Data analysis techniques used are pattern matching, explanation and time series analysis. The results of the study show that prior to the counseling process the counselee was still at the narcissistic level where there were several aspects such as exaggerating achievements and talents, always needing admiration and praise, fantasizing about success, beauty, unlimited fame, considering oneself special and unique, feeling entitled receive special treatment (associated with classy institutions), feel entitled to special treatment or must follow their wishes, unable to empathize, jealous, behave arrogantly, arrogantly and arrogantly. Implementation of individual counseling self-control techniques carried out six meetings and three stages, namely the initial stage, the main stage and the final stage. The picture after individual counseling with self-control techniques has changed where counselee "C" can slowly control himself by doing positive activities, no longer boasting, slowly starting to realize that what he did before had a bad impact on him.